GAMBARAN IMPLEMENTASI STIKER PROGRAM PERENCANAANPERSALINAN DAN PENCEGAHAN KOMPLIKASI (P4K) DI WILAYAH KERJA UPTD UNIT PUSKESMAS BULUSPESANTREN II KABUPATEN KEBUMEN - Eni Indrayani; Y Yamoto; Eti Sulastri (Jurnal Ilmiah Kesehatan Keperawatan, 2016)
The government’s efforts to r Maternal Mortality Rate (MMR) and the Infant Mortality Rate (IMR) in Indonesia in reality still far away from the expected target, so as to accelerate the decline in maternal and infant mortality is to implement planning and prevention of complications of childbirth (P4K) through the installation of childbirth stickers on all pregnants house because it is expected to find a best way to save the pregnants, childbirth, post partum, and newborn babyThis aim of this study is to determine how the implementation of mounting stickers and Prevention Program Planning Maternity Complications (P4K) in the Work Area Public Health Center of Buluspesantren II Kebumen in 2013.This research uses descriptive method with a sampling of the total sampling.Analysis of data using univariate data analysis. It is descriptive statistical techniques. Based on research conducted, P4K stickers implementation is not good, as many as 75 respondents (76, 5%) good implementation P4K stickers, showed that all respondents, amounting to 98 pregnant women (100%) have a good level of knowledge, a majority of 23 respondents (23.5%), all respondents (98 pregnant) do not experience obstacles in the implementation of the sticker P4K Keywords: Pregnant, Knowledge, P4K Sticker